A companion to Thomas Jefferson - Cogliano, Francis D. (Malden, MA : Wiley-Blackwell, 2012)
"A Companion to Thomas Jefferson presents a comprehensive assessment and overview of the life and legacy of Thomas Jefferson through a collection of essays grounded in the latest scholarship. Works from more than thirty leading scholars explore specific themes concerning the extraordinary life and times of the influential Founding Father and third U.S. President. Jefferson's wide range of interests and expertise, are explored, along with his lengthy and multifaceted public career. Other essays delve into elements of Jefferson's private life, including his controversial relationship with Sally Hemings. The essays also consider Jefferson and American democracy, slavery, Native Americans, and his writings such as the Summary View of the Rights of British America, The Declaration of Independence, and Notes on the State of Virginia. A Companion to Thomas Jefferson represents a comprehensive portrait of the elusive and contradictory figure who continues to hold sway in the public imagination and occupies a central place in American history"--
Front Matter -- Jefferson's Life and Times. Jefferson and Biography / Annette Gordon-Reed -- Jefferson's Virginia / Michael A McDonnell -- Thomas Jefferson and / Kristofer Ray -- The Declaration of Independence / Robert G Parkinson -- b3(BI have knownb4(B: Thomas Jefferson, Experience, and / Peter Thompson -- The Virginia Statute for Establishing Religious Freedom / John A Ragosta -- A Republican Reformation: Thomas Jefferson's Civil Religion and the Separation of Church from State / Johann N Neem -- The Paris Years of Thomas Jefferson / Iain McxLean -- Jefferson as Party Leader / Todd Estes -- A Qualified Revolution: The Presidential Election of 1800 / Joanne B Freeman -- The (Federalist?) Presidency of Thomas Jefferson / Robert M S McDonald -- From b3(BFloating Ardorb4 (Bto the b3(BUnion of Sentimentb4(B: Jefferson on the Relationship between Public Opinion and the Executive / Jeremy D Bailey -- Jefferson and International Relations / Leonard J Sadosky -- Jefferson in Retirement / Andrew Burstein -- Themes. Thomas Jefferson and Native Americans / Andrew Cayton -- Thomas Jefferson: Planter and Farmer / Lucia Stanton -- Thomas Jefferson and Slavery / Cassandra Pybus -- Sally Hemings / Catherine Kerrison -- Thomas Jefferson and Affairs of the Heart / Billy L Wayson -- Thomas Jefferson and John Adams / Richard Samuelson -- The Libraries of Thomas Jefferson / Kevin J Hayes -- Jefferson and the Law / David Thomas Konig -- Thomas Jefferson, Cosmopolitanism, and the Enlightenment / Hannah Spahn -- Thomas Jefferson and the Ancient World / Caroline Winterer -- Jefferson and American Democracy / Peter S Onuf -- Thomas Jefferson and Constitutionalism / R B Bernstein -- Political Economy / Max M Edling -- Jefferson and Education / Cameron Addis -- Legacy. History, Politics, and the Self: Jefferson's b3(BAnasb4 (Band Autobiography / Matthew E Crow -- b3(BFor Generations to Comeb4(B: Creating the b3(BDefinitiveb4 (BJefferson Edition / Barbara B Oberg, James P McClure -- Preservation and Education: Monticello and the Thomas Jefferson Foundation / Francis D Cogliano -- Jefferson's Legacy: The Nation as Interpretative Community / Brian Steele -- Thomas Jefferson in the Twenty-First Century / Jack N Rakove -- Bibliography -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826; Jefferson, Thomas -- 1743-1826; 1783-1809; Presidents -- United States -- Biography; HISTORY -- United States -- Colonial Period (1600-1775); BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- State & Local -- General; Politics and government; Presidents; United States -- Politics and government -- 1783-1809.; United States; Electronic books; Biography; Electronic books